2018
DOI: 10.3174/ajnr.a5735
|View full text |Cite
|
Sign up to set email alerts
|

Application of Reduced-FOV Diffusion-Weighted Imaging in Evaluation of Normal Pituitary Glands and Pituitary Macroadenomas

Abstract: FOV optimized and constrained undistorted single-shot DWI helps acquire high-resolution images of normal pituitary glands and pituitary macroadenomas with relatively few susceptibility artifacts in a clinically feasible scan time. This sequence might be helpful for evaluating the consistency of pituitary macroadenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Previous studies found that the advantages of rFOV DWI were better image quality than conventional DWI in other organs. 16,17 For quantitative DCE-MRI parameters, this study found that K trans and k ep could differentiate low-risk TETs, high-risk TETs, and thymic carcinoma. Advanced stage TETs had higher K trans and k ep than early stage TETs.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous studies found that the advantages of rFOV DWI were better image quality than conventional DWI in other organs. 16,17 For quantitative DCE-MRI parameters, this study found that K trans and k ep could differentiate low-risk TETs, high-risk TETs, and thymic carcinoma. Advanced stage TETs had higher K trans and k ep than early stage TETs.…”
Section: Discussionmentioning
confidence: 85%
“…It may be due to the different image quality between the two DWI methods. Previous studies found that the advantages of rFOV DWI were better image quality than conventional DWI in other organs 16,17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Помимо стандартных анатомических изображений, важную диагностическую информацию несут диффузионно-взвешенные изображения с построением карт измеряемого коэффициента диффузии, которые входят в стандарт обследования пациента и могут быть полезны при диагностике инфаркта или апоплексии гипофиза [47], выявлении кистозных участков в объемном образовании [56] и раннем обнаружении остаточных фрагментов опухоли [57]. Оправданно применение диффузионно-взвешенных импульсных последовательностей с меньшей чувствительностью к источникам артефактов, таких как последовательности с уменьшенным полем обзора (FOCUS, ZOOMit, iZOOM) [58].…”
Section: Russian Journal Of Neurosurgeryunclassified